Assessment of animal diseases caused by bacteria resistant to antimicrobials: Poultry. (24th December 2021) - ,; Nielsen, Søren Saxmose; Bicout, Dominique Joseph; Calistri, Paolo; Canali, Elisabetta; Drewe, Julian Ashley; Garin‐Bastuji, Bruno; Gonzales Rojas, Jose Luis; Gortazar Schmidt, Christian; Herskin, Mette; Michel, Virginie; Miranda Chueca, Miguel Angel; et al.
Abstract: In this opinion, the antimicrobial‐resistant bacteria responsible for transmissible diseases that constitute a threat to poultry health have been assessed. The assessment has been performed following a methodology based on information collected by an extensive literature review and expert judgement. Details of the methodology used for this assessment are explained in a separate opinion. A global state of play is provided for: Avibacterium (Haemophilus) paragallinarum, Bordetella avium, Clostridium perfringens, Enterococcus faecalis and Enterococcus cecorum, Erysipelothrix rhusiopathiae, Escherichia coli, Gallibacterium spp., Mycoplasma synoviae, Ornithobacterium rhinotracheale, Pasteurella multocida, Riemerella anatipestifer and Staphylococcus aureus . Among those bacteria, EFSA identified Escherichia coli, Enterococcus faecalis and Enterococcus cecorum with ≥ 66% certainty as being the most relevant antimicrobial resistant bacteria in the EU based on the available evidence. The animal health impact of these most relevant bacteria, and their eligibility for being listed and categorised within the Animal Health Law Framework, will be assessed in separate scientific opinions.